Impact of the economic crisis on the health of older persons in Spain: research clues based on an analysis of mortality. SESPAS report 2014 - Tarik Benmarhnia; Maria-Victoria Zunzunegui; Alicia Llácer; Francois Béland (Elsevier, 2014)
Older adults are seldom considered in studies on the health impact of economic recessions or crises. However, they constitute a population group that is highly vulnerable to decreases in investment in health and social services and social security. Our aim is to examine the relationship between the economic crisis starting in 2008 and the health status of older adults in Spain. More specifically, we analyze changes in trends of mortality in relation to the crisis, the specific impact of winter on mortality and gender differences in the crisis' impact on mortality. Using data from the National Institute of Statistics of Spain on people over 60 years of age, the number of monthly deaths by age and sex from January 2005 to December 2012 was analyzed. Interrupted time series analyses and the "difference in differences" method were used. During the crisis, for adults 60 years and older: 1) the observed mortality seems to be decreasing at a slower rate than what would have been expected in the absence of the crisis; 2) there has been an increase in winter mortality; 3) the impact of the crisis has been greater for female than for male mortality. These results suggest sizable effects of the economic crisis on the mortality of older adults and argue for research done using more detailed analyses integrating economic indicators.